Genially and Flippity DGBL for Vocabulary Mastery Across Students' Motivation Levels - Re Tali Imani; Rudi Hartono; Rini Susanti Wulandari (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Lack of motivation and vocabulary are major barriers to students in mastering English. Therefore, it is necessary to implement a strategy that is attractive and effective in supporting students in mastering vocabulary, and that is congruent with this era. There may be several solutions that the teachers could implement to create an attractive learning process, such as building a joyful class environment by applying Digital Game-Based Learning (DGBL) in the English Classroom. Teaching and learning through digital aids could foster students’ focus and interest in the classroom. The purposes of this study are 1) explain the effectiveness of Genially and Flippity to enhance students’ vocabulary mastery; 2) investigate the effect of motivation level on students’ vocabulary mastery; 3) examine whether there is an interaction between teaching method and motivation level in enhancing students’ vocabulary; 4) explain the use of Genially DGBL and Flippity DGBL to teach vocabulary to students with different motivation level. This type of research design encompasses a mixed-methods design. It follows the principles of an embedded mixed-method design. This study was conducted at MTs Minhajut Tholabah. This study consists of two independent variables that are Genially DGBL and Flippity DGBL, one dependent variable that is students’ vocabulary mastery, and one moderator variable that is students’ motivation. The study population comprises 8th-grade students at MTs Minhajut Tholabah. There was an experimental class that was nearly homogeneous in its achievement by using purposive sampling. The study sample consists of 23 students, divided into high- and low-motivation groups. Thus, the experimental class was taught using Genially and Flippity. The researcher used the requisite tests (normality, homogeneity, and linearity) to analyze the data, and Analysis of Covariance (ANCOVA) to test the hypotheses. The results show that Genially and Flippity are effective in enhancing vocabulary. Meanwhile, there is no significant difference between Genially DGBL and Flippity DGBL in teaching vocabulary to low- and high-motivated students.